Desempenho agronômico de híbridos de milho em função de espaçamentos e densidades populacionais em três locais - Gonçalves, Marcio Leandro (2008)
A study was conducted with the objetive to evaluate the effect of spacing between the plantation rows (0.45, 0.68 and 0.90 m) on plants population density of (50.000, 60.000, 70.000 and 80.000 plants ha-¹) about the grain productivity of three hibrid corn (Zea mays L.) A field experiment was conducted from September 10 to April 10/2008 in three different environments with different height, in Goioerê, Toledo and Cascavel localized in the west of Parana State. The design utilized was of randomized blocks into subdivided parcels. The spacing were placed in the main parcel and the population density and hybrids in sub parcels in a factorial schema. Biometric variables such as plant height, height of insertion of the first spike and diameter of stem and the components of production, number of rows, number of grains per spike, mass of grains per spike, the mass spike and productivity, were evaluated. Was no effect of row spacing, obtaining the maximum grain yield with the spacing of 0.57 m between rows, regardless of location. There was positive interaction between the environmental effect of plant population. The positive response to the increase of population in the Toledo plant was directly related to the level of soil fertility. In Cascavel Goioerê and no significant difference to the increase in population from 50,000 to 80,000 plants ha-1. In all locations the hybrid AS 1570 showed higher productivity of hybrid AS 1565 and AS 1575